Ethical Implications of War-Borne Disabling Casualties - Iozzio, Mary Jo (Journal of religion, disability & health, 2008)
Questions of justice in the face of diverse casualties require attention to soldiers and civilians with disabilities: the silence that surrounds both the deaths and disabling casualties of soldiers and civilians occurring at rapid pace in war is scandalous; healthcare services must be responsive to the needs of soldiers with disabling casualties returning from their tours of duty. The tradition of Catholic social teaching and its preferential option for the poor provides an effective decision-making matrix in determining the response to these needs. The crises in healthcare may be relieved by universal access based on the option for those who are disabled.